EFFECT OF DIFLUOROMETHYLORNITHINE ON THYROID FUNCTION IN RATS - Rehman, Rehana; Khan, Rakhshaan; Soomro, Muhammad Saleh; Aslam, Muhammad Aslam (Journal of Ayub Medical College Abbottabad, 2009)
Background: A variety of stimuli cause a rapid increase in polyamine synthesis by increasing an enzyme ornithine decarboxylase required for the biosynthetic pathway of protein synthesis. Difluoromethyl ornithine is a selective inhibitor of this enzyme and hence arrests cell replication strikingly. Its effects on thyroid gland are studied with respect to change in animal’s weight and levels of Triiodothyronine, Thyroxine and Thyroid stimulating hormone. The study was conducted to evaluate the inhibitory effects of Di-fluoromethyl ornithine (DFMO) administration on polyamine metabolism of thyroid gland in rats. Methods: The study was conducted on rats weighing 248 to 320 grams, divided into control and DFMO treated group. A dose of 50 mg/rat was administered subcutaneously to the treated group for 5 consecutive days and placebo (normal saline) injections to control group. On sixth day, blood was collected by cardiac puncture and serum was separated. Serum T3, T4 and TSH were analyzed with the help of radioimmunoassay in both groups. Results: In treated group there was a fall in T3, T4 concentration with significant rise in TSH concentration as compared to control group. Conclusion: DFMO (Difluoro methyl ornithine) decreases cellular proliferation of thyroid gland as is assessed by decrease in thyroid hormone levels. The hypothalamo pituitary thyroid axis however remains intact as is shown by a feedback rise in TSH concentration. DFMO can thus be employed for anti-neoplastic clinical trials on account of interference with activity of ODC (Ornithine Decarboxylase) fundamental for polyamine biosynthesis. Keywords: DFMO, ODC, thyroid, rats, radioimmunoassay